2021
DOI: 10.3390/math9172083
|View full text |Cite
|
Sign up to set email alerts
|

Energy Crisis in Pakistan and Economic Progress: Decoupling the Impact of Coal Energy Consumption in Power and Brick Kilns

Abstract: This study aims to examine the impact of coal energy consumption on the economic progress in Pakistan by using annual time series data during 1972–2019. Three-unit root tests were employed to rectify the variables’ stationarity. The quantile regression approach with the extension of cointegration regression test was utilized to check the variables interaction with the economic progress. The outcomes of the quantile regression uncover that coal energy consumption in power sector and coal energy consumption in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…Previous studies identified that urbanization (Balsalobre-Lorente et al, 2021;Qader et al, 2021), institutional quality (Usman and Jahanger, 2021), renewable/nonrenewable/total energy consumption (Usman et al, 2020;Hussain and Rehman, 2021;Regmi and Rehman, 2021;Rehman et al, 2021a;Rehman et al, 2021b), and trade (Rehman et al, 2021c;Rehman et al, 2021d; are more influencing factors that affect CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies identified that urbanization (Balsalobre-Lorente et al, 2021;Qader et al, 2021), institutional quality (Usman and Jahanger, 2021), renewable/nonrenewable/total energy consumption (Usman et al, 2020;Hussain and Rehman, 2021;Regmi and Rehman, 2021;Rehman et al, 2021a;Rehman et al, 2021b), and trade (Rehman et al, 2021c;Rehman et al, 2021d; are more influencing factors that affect CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While this research focuses on the implication of economic growth and external financial flows on material consumption, previous studies investigated the role of industrialization and economic progress, energy consumption and intensity, natural resource depletion, and financial development (Khan et al 2021;Rehman et al 2021aRehman et al , 2021b. These studies used time-series data analysis, causality analysis, and autoregressive-distributed lag models to explain the relationship between variables, generating a methodological contribution pertinent to research focusing on the environment-sustainability-development-energy nexus.…”
Section: A Brief Review Of the Literaturementioning
confidence: 99%
“…For atmospheric protection, some emissions have adverse effects on the environment, especially some emissions associated with fossil fuels (polluting energy) like carbon dioxide and other greenhouse gases (Rehman et al, 2021c). However, the total consumption of some specific energy, such as coal in Pakistan, has a productive relation to economic growth (Rehman et al, 2021d). Hence, the huge usage of fossil energy in some developing economies, including China, generates great environmental pressure and will remailn tied to economic development for a long period.…”
Section: Implementing Proper Policies With the Vision Of Green And Su...mentioning
confidence: 99%